KONSEP DAN IMPLEMENTASI PENDEKATAN DEEP LEARNING DI SEKOLAH DASAR - Nurul, Aulia; Iskandar, Sofyan; Amalia, Mutiah; Putri Fasya Naziha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the integration of the concept of deep learning with the implementation of a learning approach that emphasizes meaningful, mindful, joyful elements in the context of elementary school education. The purpose of this research is to analyze how the concept of deep learning can be effectively implemented at the primary school level. The method used is a qualitative approach based on literature and content analysis from various scientific sources and educational practices. The results of the analysis show that learning that applies a deep learning approach that is joyful, meaningful, and mindful can increase student engagement, strengthen concept understanding, and support cognitive and emotional development. Effective implementation requires the support of teachers who understand modern pedagogical approaches, the availability of adequate technology, and a curriculum that is adaptive to changing times.